Exploring the Painting Artist Perceptions Towards Their Career Sustainability in Pokhara - Adhikari, Ujjwal (Journal of Interdisciplinary Studies, 2023)
This qualitative study investigates sustainable career perceptions among painting artists in Pokhara, utilizing pseudo names for participants: Ram, Hari, Purnima, and Kalpana. Through purposive sampling, semi-structured interviews was conducted to gather insights. Thematic analysis was applied to identify patterns and themes within the data. Ethical considerations, such as informed consent and participant confidentiality, was strictly followed. By employing these methods, this study shed light on the intricacies of sustaining an art career in Pokhara. This study reveals how personal passion and adaptability influence painting artists’ careers in Pokhara, emphasizing their contribution to personal fulfillment, the art community, and society. It underscores the importance of resilience, personal branding, financial awareness, and gender dynamics in navigating challenges. Art communities and organizations can use the insights of this study to develop collaborative initiatives that support artists, encourage networking, and nurture emerging talents, ultimately contributing to a thriving art community.